“Epidemioligía de la alternariasp en tres clones de cebolla china (allium fistulosum) en Lamas, San Martín” - Paredes Campos, Jose Martin (2014)
The objectives of the present experimental work were to identify the factors epidemiologists by means of the evaluation of the incidence and the severity that the fungus in three clones of Chinase onion causes during its fenológico period; to determine the minimum relativa humidity, elasticity effect and Maxima and precipitation with the incidence and severity of the disease; the same one, which the Pacific " of property of Mr. Segundo Najar, located was developed in Fundo " on the district and province of You lick, department of San Martín, with a 200 precipitation of 1 mm/a6no and one temperatura 22.39 average of ºC. Used experimental design was the design of Latin Square of 3 columns and 3 rows. The effect in Creole Onion with incidence registered to 36, 43, 50, 57 and 64 days of seedtime registered the smaller incidence of the disease in plants, whereas the red clone onion Chiclayana and white onion reached the greater percentage of incidence of the disease in leaves. The clone White Onion shows the greater percentage of the number of spots by leaf and with smaller incidence the clone Creole onion. The clone Creole Onion, shows a greater resistance the disease severity, whereas the clones Chiclayana Onion and white Onion show a greater susceptibility the disease. Also it is necessary to mention, that the greater yield of Creole onion with 20 600.00 was obtained kg/ha., and so that the harvest prematura befare is observad a greater incidence.